2017
DOI: 10.1177/0163443717736118
|View full text |Cite
|
Sign up to set email alerts
|

Netflix, Amazon, and branded television content in subscription video on-demand portals

Abstract: Branding has been described as the defining industrial practice of television’s recent past. This article examines publicly available industry documents, trade press coverage, and executive interviews to understand the place of traditional television network branding in subscription video on-demand (SVOD) portals as represented by Amazon and Netflix. Focusing on materials relating to licensed rather than original content and this content’s role within the US domestic SVOD market, two distinct approaches emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0
16

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(80 citation statements)
references
References 17 publications
1
63
0
16
Order By: Relevance
“…Beberapa media yang telah menerapkan media digital berbayar seperti The New York Times dan The Washington Post (Hallin & Mancini, 2016) (Dhiya & Fadilah, 2018). Menarik untuk meneliti mengenai penerapan media digital berbayar di Indonesia ketika mayoritas media digital masih belum menarik biaya dan perilaku konsumsi informasi masyarakat masih mencari yang bebas biaya.…”
unclassified
“…Beberapa media yang telah menerapkan media digital berbayar seperti The New York Times dan The Washington Post (Hallin & Mancini, 2016) (Dhiya & Fadilah, 2018). Menarik untuk meneliti mengenai penerapan media digital berbayar di Indonesia ketika mayoritas media digital masih belum menarik biaya dan perilaku konsumsi informasi masyarakat masih mencari yang bebas biaya.…”
unclassified
“…By adapting the core concept of the subscription‐based business, at present, there are numerous SBRS in operation in the U.S. For instance, Noorda () reported that SBRS have experienced exponential growth, with demands for SBRS increasing almost 30 times between 2013 and 2016. There are different SBRS, which are industry‐specific such as publishing books and magazines (Noorda, ), beauty and fashion (Bhatt, ; Sivathanu, ; Woo & Ramkumar, ), and video‐streaming such as Netflix and Amazon Prime (Wayne, ). However, the present study focuses exclusively on beauty‐related SBRS like Birchbox, Ipsy, Glossybox, and others.…”
mentioning
confidence: 99%
“…On the contrary, the TV Series are in an absolute boom, with million-dollar productions, whose success and cache has displaced actors and actresses of great reputation to the silver screen, and with great acceptance among the public, as the ones cited above. What we are trying to suggest here is that the filmmaking industry might be following the steps of the music one, and now undergoing the same evolution and mutation process, from an old business model to a new one, driven by new technologies (subscription video on demand) 64 and consumer tastes, in a new scenario where, again, internet is serving as a profitable and fast-growing channel for a legal offer at fair and appealing price point.…”
Section: Questions Of Wtp [Willingness To Pay] For Both the Number Ofmentioning
confidence: 99%